Radical reaction control in the AdoMet radical enzyme CDG Synthase (QueE): consolidate, destabilize, accelerate - Jäger, Christof M.; Croft, Anna K. (Wiley-VCH Verlag, 2017)
Controlling radical intermediates and thus catalysing and directing complex radical reactions is a central feature of S-adensosylmethionine (SAM)-dependent radical enzymes. We report ab initio and DFT calculations highlighting the specific influence of ion complexation, including Mg2+, identified as a key catalytic component on radical stability and reaction control in 7-carboxy-7-deazaguanine synthase (QueE). Radical stabilisation energies (RSEs) of key intermediates and radical clock-like model systems of the enzyme-catalysed rearrangement of 6-carboxytetrahydropterin (CPH4), reveals a directing role of Mg2+ in destabilising both the substrate-derived radical and corresponding side reactions, with the effect that the experimentally-observed rearrangement becomes dominant over possible alternatives. Importantly, this is achieved with minimal disruption of the thermodynamics of the substrate itself, affording a novel mechanism for an enzyme to both maintain binding potential and accelerate the rearrangement step. Other mono and divalent ions were probed with only dicationic species achieving the necessary radical conformation to facilitate the reaction.